WORLD-TALK VIS-A-IS GOD-TALK Reflections from a Theistic Reading of Kant - George Kulangara (Journal of Dharma, 2012)
Most of what people talk pass for world-talk. Most of the talk we engage in is about something in the world. A meaningful talk about a thing requires that any veil of non-clarity be lifted from the status of the thing. Once we put ourselves in a Kantian world, this requirement introduces before us a huge problem as Kant has neatly divided the world into a phenomenal world and a noumenal world. Kant has advocated that we limit our talk to the phenomenal so that our talk bears the stamp of meaningfulness. But the phenomenal as Kant has envisaged is a construction by our mind. It would then mean that unless it has a reference to the real world of the noumenal, what we take to be our talk about the world will amount to nothing more than a talk about ourselves. The situation can be redeemed only by granting a determinate status to the noumenal world which will in turn prop up the phenomenal. There are valid grounds to suggest that Kant does precisely that. The noumenal in his philosophy is the world as seen by God. Hence let me propose that no real world-talk is possible without a God-talk.